Human-machine interaction and forms of human communication (Research, Society and Development, 2021)
Communication is the main means of propagating culture and a tool for the integration of human society. In recent times, the advancement of information technology has been enhancing this medium. The purpose of this article is to analyze a way and means that people use as machines to communicate and interact. The Human-Machine Interaction (HMI) is conceived and treated in the article as the central theme of this study. The main information is taken from scientific articles, researches, books and reports. It uses a structure that denounces as problems involving ethics, evolution, dependence and other impacts of the HMI, proposing a type survey, in the form of a questionnaire, with questions related to the topic. The results indicate that the population of the young population is interested in and has relationships with digital machines, generating a dependency on the part of this population in relation to these machines. Therefore, it is generally concluded that the acceptance and appreciation of the Human-Machine Interaction in the world is intensifying.